All Days 2004
DOI: 10.4043/16294-ms
|View full text |Cite
|
Sign up to set email alerts
|

Design and Installation of the Valhall Piggyback Structures

Abstract: This paper describes the design development and installation of a novel concept used to repair the piles at Valhall Water Injection Platform in the Southern Norwegian Sector of the North Sea. The paper describes the concept, design principles, the tolerances required to account for known and potential dimensional variations, a test programme to verify key activities and the installation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…It was reported that the major reason for pile collapse was the damage propagation starting from the pile tip. A similar case was observed at Valhall water injection platform where five out of eight skirt piles were damaged during installation [8].…”
Section: Motivationsupporting
confidence: 62%
“…It was reported that the major reason for pile collapse was the damage propagation starting from the pile tip. A similar case was observed at Valhall water injection platform where five out of eight skirt piles were damaged during installation [8].…”
Section: Motivationsupporting
confidence: 62%